Counseling About Providing Preparation Education for Menopause at Dusun Seno, Padang Cermin Village, Selesai District, Langkat Regency - Seri Wahyuni Harahap; Sri Rezeki; Kiki Khoiriyani; Erin Padilla Siregar (IJCS: International Journal of Community Service, 2023)
Menopause occurs at an average age of 51 years. These symptoms appear since the premenopausal period. Premenopause, namely the age group between 48-55 years followed by symptoms that often arise three to ten years before the arrival of menopause with various complaints, both physical and psychological complaints. This study aims to identify knowledge, attitudes and the relationship between knowledge and attitudes of premenopausal mothers in dealing with changes during menopause in Seno Village, Padang Cermin Village, Prestasi District, Langkat District. Number of women aged continued in 2025 on the Asian continent will increase from 107 million people to 373 million people. Premenopausal symptoms include 40% hot flashes, 38% difficulty sleeping, 37% get tired faster at work, 35% more often forget, 33% irritable, 26% joint pain and 21% frequent headaches excessive. The purpose of community service is to provide education about signs and symptom, stages menopause And management as preparation in a manner early face menopause. In family when a Mother Healthy, in meaning can minimize symptom menopause with knowledge Which has accepted on education preparation face menopause so activity family will walk with Good. Method: Education preparation face menopause use method lecture And discussion with media powerpoint. Results: The community service participants were very enthusiastic about participating in the activity, and the discussion was ongoing well and smoothly. Conclusion : Preparatory education dealing with menopause has been done, the participants were very enthusiastic about the activity, there were several questions submitted by the participants. Providing education as a form of transfer of knowledge is expected to be carried out routinely to the woman he hopes for after participating in this activity complaints during menopause can reduce and quality of life will be felt on Woman itself.